2022
DOI: 10.1371/journal.pone.0264697
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the adverse events following immunization surveillance system, Ghana, 2019

Abstract: Background With over 80% of children worldwide vaccinated, concerns about vaccine safety continues to be a public health issue. Ghana’s Adverse Events Following Immunization surveillance started in 1978 with the objective to promptly detect and manage AEFI cases either real or perceived. Periodic evaluation of the surveillance system is critical for optimal performance; hence we evaluated the system to assess its attributes, usefulness and system’s performance in meeting its objectives. Methods A case of AEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…Similarly, more than 40% of health workers alluded to time constraints and lack of belief in the event being related to immunization. Similar findings have been documented in studies conducted in the country and other countries [16,[21][22][23][24]. These are critical reasons that require the attention of the health authorities to address.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similarly, more than 40% of health workers alluded to time constraints and lack of belief in the event being related to immunization. Similar findings have been documented in studies conducted in the country and other countries [16,[21][22][23][24]. These are critical reasons that require the attention of the health authorities to address.…”
Section: Discussionsupporting
confidence: 85%
“…Though majority of the health workers had good perception of AEFI reporting like findings from studies in other states [21], the study further identified good knowledge of AEFI and routine receipt of feedback from the higher administrative level as predictors of good perception on AEFI amongst providers. This further buttressed fact that beyond the health systems requesting these reports from the service delivery points, surveillance systems including that of AEFI is a two-way process whereby reporting should be followed by feedback on the outcome of the reports [2,22,25]. The global surveillance guideline indicates that irrespective of the outcome of reported AEFI cases, findings from the investigation and lessons learnt from the causality assessment of serious cases, should provide insights on the immunization programme for the technical team and immunization programme managers and there should be prompt and clear communication and with all stakeholders including feedback to the healthcare workers that reported as well as the community on the next line of action [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low AEFI reporting is a problem in most LMICs leading to scanty safety information on vaccines that affects the quality of causality assessment reports. 31 HCPs at vaccination centers have the responsibility of educating mothers about both the common and self-limiting AEFIs as well as rare and unexpected ones while urging them to report. In the current study, about 70% of the participants did not inform mothers of infants who received the BCG vaccine and this requires significant improvement.…”
Section: Discussionmentioning
confidence: 99%
“…CDC Evaluation Guidelines”) framework [ 38 ]. The U.S. CDC Evaluation Guidelines has been used and validated in studies to evaluate surveillance programs across the world, including Brazil [ 39 ], Ghana [ 40 ], Jordan [ 41 ], Yemen [ 42 ], and others [ 43 ]. The U.S. CDC Evaluation Guidelines considers nine metrics: i) simplicity, ii) flexibility, iii) data quality, iv) acceptability, v) sensitivity, vi) predictive value positivity, vii) representativeness, viii) timeliness, and ix) stability.…”
Section: Methodsmentioning
confidence: 99%